Meningkatkan Prestasi Belajar Bahasa Indonesia Dengan Menerapkan Model Pengajaran Kolaborasi Pada Siswa IV SD - Almurni Almurni (Yayasan Darusssalam Bengkulu, 2020)
The learning process that involves materials, methods, teaching aids and so on must undergo changes towards renewal (innovation). Teachers are required to be more creative and innovative. Especially in determining the appropriate learning model and method will determine the success of students in the formation of life skills. Students' life skills are also expected to emerge when learning Indonesian. Therefore the purpose of this study is to find out the improvement of Indonesian learning achievement after the implementation of the collaborative teaching model and to determine the effect of motivation to learn Indonesian after applying the collaborative teaching model. This research method uses action research as much as two cycles. Each cycle consists of four stages: design, activity and observation, reflection, and revision. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analyst found that student achievement has increased from cycle I to cycle II namely, cycle I (51%) and cycle II (89%). The conclusion is that the collaborative teaching model can positively influence the achievement, interest, attention and participation, motivation of learning student of Public Elementary School 03 Mukomuko City, as well as this learning model can be used as an alternative learning Indonesian achievement.